2019
DOI: 10.1039/c8sc05258a
|View full text |Cite
|
Sign up to set email alerts
|

Proline bulky substituents consecutively act as steric hindrances and directing groups in a Michael/Conia-ene cascade reaction under synergistic catalysis

Abstract: In this study, we report a highly stereoselective and versatile synthesis of spiro pyrazolones, promising motifs that are being employed as pharmacophores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The general applicability of this protocol was investigated and it was found that the reaction proceeds smoothly for enals 5 and pyrazolones 22 having different electronic and steric effects (Scheme 14). [45] In the same year, this group disclosed the synthesis of spiroazlactone (spirooxazolone) derivatives 25 via asymmetric cyclization of enals 5 with vinylcyclopropane azlactones 24. The reaction is efficiently catalyzed by the combination of tris(dibenzylideneacetone) dipalladium(0) and chiral secondary amines.…”
Section: Combining Pd and Aminocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general applicability of this protocol was investigated and it was found that the reaction proceeds smoothly for enals 5 and pyrazolones 22 having different electronic and steric effects (Scheme 14). [45] In the same year, this group disclosed the synthesis of spiroazlactone (spirooxazolone) derivatives 25 via asymmetric cyclization of enals 5 with vinylcyclopropane azlactones 24. The reaction is efficiently catalyzed by the combination of tris(dibenzylideneacetone) dipalladium(0) and chiral secondary amines.…”
Section: Combining Pd and Aminocatalystsmentioning
confidence: 99%
“…The general applicability of this protocol was investigated and it was found that the reaction proceeds smoothly for enals 5 and pyrazolones 22 having different electronic and steric effects (Scheme 14). [45] …”
Section: Combining Aminocatalysis and Transition Metal Catalysismentioning
confidence: 99%
“…The corresponding tandem products were in high yields and with excellent enantioselectivities [80]. Silyl ethers of diarylprolinol were also used in the highly stereoselective synthesis of spiro pyrazolones via Michael/Conia-ene cascade reaction [82] and in the synthesis of biaryl atropoisomers via domino Michael-Henry reaction affording the substituted nitrocyclohexanecarbaldehydes [83].…”
Section: Asymmetric Michael Reactionsmentioning
confidence: 99%
“…In 2019, Herrera, Rios, Veselý, and co-workers described a tandem reaction of 4-propargylpyrazolones with ,-unsaturated aldehydes (Scheme 27). 58 In particular, this example consists of a Michael addition catalyzed by the Jørgensen-Hayashi catalyst 59 followed by a Pd(II)-catalyzed Conia-ene cyclization. The corresponding spirocyclic products were obtained in low to moderate diastereoselectivities (up to 5.6:1 dr), low to high yields (up to 93%), and excellent enantiomeric excess (up to 96% ee).…”
Section: Asymmetric Synthesis Of Chiral Spiropyrazolones Bearing a Fumentioning
confidence: 99%